Higher Class of Obesity Is Associated With Delivery of Higher Tidal Volumes in Subjects With ARDS. - Grim, Chloe C. A.; Helmerhorst, Hendrik JF; Schultz, Marcus J.; Winters, Tineke; van der Voort, Peter H. J.; van Westerloo, David J.; de Jonge, Evert (Respiratory Care, 2020)
BACKGROUND: Little is known to what extent attitudes of ICU clinicians are influenced by new insights and recommendations to be more conservative with oxygen therapy. Our aim was to investigate whether implementation of a conservative oxygenation guideline structurally changed self-reported attitudes and actual clinical practice. METHODS: After the implementation of a conservative oxygen therapy guideline in 3 teaching hospitals in the Netherlands, ICU clinicians were surveyed regarding their attitudes toward oxygen therapy. The survey results were compared with survey results taken before the introduction of the new guideline. Arterial blood gas analysis data and ventilator settings were retrieved from all patients admitted to the participating ICUs in the studied period, and changes after implementing the guideline were assessed. RESULTS: In total, 180 ICU clinicians returned the survey. Compared to before implementation of a conservative oxygen guideline, more clinicians chose a preferred PaO2 and an oxygen saturation measured from an arterial sample (SaO2) limit after implementation of the guideline. In general, clinicians reported a more conservative approach toward management of FIO2 and less frequently increased the FIO2. In the period after the active implementation of the guideline, 5,840 subjects were admitted to the participating ICUs and 101,869 arterial blood gas analyses were retrieved. Actual practice changed with overall lower oxygenation levels (median PaO2 77.93 mm Hg, compared to 86.93 mm Hg before implementation) of arterial blood and a decrease of PEEP and FIO2. CONCLUSIONS: Implementing a conservative oxygenation guideline was an effective method that changed self-reported attitudes and actual clinical practice and improved adherence to conservative oxygenation targets in a short period of time.